2008
DOI: 10.1002/prot.22305
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and dynamics of amyloid peptide oligomerization are sequence dependent

Abstract: Aggregation of the full‐length amyloid‐β (Aβ) and β2‐microglobulin (β2m) proteins is associated with Alzheimer's disease and dialysis‐related amyloidosis, respectively. This assembly process is not restricted to full‐length proteins, however, many short peptides also assemble into amyloid fibrils in vitro. Remarkably, the kinetics of amyloid‐fibril formation of all these molecules is generally described by a nucleation‐polymerization process characterized by a lag phase associated with the formation of a nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 50 publications
12
112
1
1
Order By: Relevance
“…While an increased β-strand from Aβ 42 -WT monomer (21%) to Aβ 40 -WT monomer (6%) correlates with the observation that Aβ 42 forms fibrils faster than Aβ 40 , a reduction of β-strand content from Aβ 42 -WT dimer (24%) to Aβ 40 -WT dimer (32%), a constant β-strand content for Aβ 40 dimer upon D7N mutation and a 50% reduction of β-strand content in Aβ 42 dimer upon D7N mutation do not contradict the basic understanding of the differences between the two alloforms. Indeed, it is well established that other physicochemical factors such as charge and hydrophobicity contribute to enhanced aggregation rates, 61 and what counts in explaining aggregation rate variation is not a Shown are the population P (in %), the mean values of the total fibril contacts (N fb ), the center of mass distance (in nm) between the 7th residues of two chains (d R7 ), the secondary structure contents (in %) using residues 1−40, the populations (in %) of intramolecular two-stranded β-sheet (iP bs 2s ), intermolecular two-stranded β-sheet (oP bs 2s ), three-stranded β-sheet (P bs 3s ), and four-stranded β-sheet (P bs 4s ). The populations of higher-stranded β-sheets are almost zero.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…While an increased β-strand from Aβ 42 -WT monomer (21%) to Aβ 40 -WT monomer (6%) correlates with the observation that Aβ 42 forms fibrils faster than Aβ 40 , a reduction of β-strand content from Aβ 42 -WT dimer (24%) to Aβ 40 -WT dimer (32%), a constant β-strand content for Aβ 40 dimer upon D7N mutation and a 50% reduction of β-strand content in Aβ 42 dimer upon D7N mutation do not contradict the basic understanding of the differences between the two alloforms. Indeed, it is well established that other physicochemical factors such as charge and hydrophobicity contribute to enhanced aggregation rates, 61 and what counts in explaining aggregation rate variation is not a Shown are the population P (in %), the mean values of the total fibril contacts (N fb ), the center of mass distance (in nm) between the 7th residues of two chains (d R7 ), the secondary structure contents (in %) using residues 1−40, the populations (in %) of intramolecular two-stranded β-sheet (iP bs 2s ), intermolecular two-stranded β-sheet (oP bs 2s ), three-stranded β-sheet (P bs 3s ), and four-stranded β-sheet (P bs 4s ). The populations of higher-stranded β-sheets are almost zero.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The properties of small multimeric aggregates (dimers to decamers) of various amyloidogenic peptide sequences have been studied by atomistic simulations and described as partially ordered, nematic structures, which are subject to rapid fluctuations and large conformational rearrangements. 41,42,[48][49][50][51][52][53][54][55][56] The obtained oligomer ensembles are described as distinct from the monomeric form 48,52,57 due to the conformational changes associated with emerging β-sheet structure. 49,56 These structural transitions were found to be accompanied by a loss of intra-peptide interactions and conformational entropy.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 MD investigations of A␤ oligomers, which are more computationally intensive, have been recently reported. [33][34][35][36][37] In general, these studies have shown that aggregation leads to considerable conformational changes in A␤ peptides. For example, we have found that interpeptide interactions in A␤ dimers induce a profound shift in the secondary structure, resulting in the conversion of helical states into ␤-strand conformations.…”
Section: Introductionmentioning
confidence: 99%